USM STUDENTS SHINE AT MYPSA NATIONAL PHARMACY QUIZ - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, May 2015 Universiti Sains Malaysia (USM) students from the School of Pharmaceutical Sciences (PPSF) have won the 7 National Pharmacy Quiz 2015 organised by the Malaysian Pharmacy Students' Association (MyPSA).